Proliferation-linked apoptosis of adoptively transferred T cells after IL-15 administration in macaques. - Carolina Berger; Michael Berger; Brian C Beard; Hans-Peter Kiem; Theodore A Gooley; Stanley R Riddell (PLoS ONE, 2013)
The adoptive transfer of antigen-specific effector T cells is being used to treat human infections and malignancy. T cell persistence is a prerequisite for therapeutic efficacy, but reliably establishing a high-level and durable T cell response by transferring cultured CD8(+) T cells remains challenging. Thus, strategies that promote a transferred high-level T cell response may improve the efficacy of T cell therapy. Lymphodepletion enhances persistence of transferred T cells in mice in part by reducing competition for IL-15, a common γ-chain cytokine that promotes T cell memory, but lymphodepleting regimens have toxicity. IL-15 can be safely administered and has minimal effects on CD4(+) regulatory T cells at low doses, making it an attractive adjunct in adoptive T cell therapy. Here, we show in lymphoreplete macaca nemestrina, that proliferation of adoptively transferred central memory-derived CD8(+) effector T (T(CM/E)) cells is enhanced in vivo by administering IL-15. T(CM/E) cells migrated to memory niches, persisted, and acquired both central memory and effector memory phenotypes regardless of the cytokine treatment. Unexpectedly, despite maintaining T cell proliferation, IL-15 did not augment the magnitude of the transferred T cell response in blood, bone marrow, or lymph nodes. T cells induced to proliferate by IL-15 displayed increased apoptosis demonstrating that enhanced cycling was balanced by cell death. These results suggest that homeostatic mechanisms that regulate T cell numbers may interfere with strategies to augment a high-level T cell response by adoptive transfer of CD8(+) T(CM/E) cells in lymphoreplete hosts.